Literature Review on the Development of Visualization Studies (2012–2022) - Tianyin Jiang; Yaxin Hou; Jaebum Yang (Engineering proceedings, 2023)
In the past decade, the visualization and transformation of data and information have attracted lots of research interest, while visualization has gradually extended to all industries. Based on the retrieval of core literature in a Web of Science search from 2012 to 2022, this study finds that these developments mainly discussed the change of visualization and its related concepts, current research hotspots, and influential journal papers. Consequently, it aims to explore research gaps and provide directional guidance for future research.